The Independent National Elections Authority as a legal guarantee for the integrity of the electoral process. - Houadeg, Issam (Journal of Human Sciences, 2020)
The electoral process is a very complicated process that is not without problems that may amount to fraud and tampering with the results, and for this the success of this process was necessary for the participation of many parties and stakeholders, whether voters or candidates with different spectrums and political orientations, or the authority entrusted with ensuring the organization of the process. The electoral process in its various stages. As an embodiment of this principle, Parliament in its two chambers (the National People’s Assembly and the National Assembly) has approved the amendment of the election law through Organic Law No. 19-08 of 14 Muharram 1441 AH corresponding to September 14, 2019 amending and supplementing Organic Law No. 16- 10 dated on Dhul Qi’dah 22 related to the electoral system, and for the first time in the history of independent Algeria, an independent national authority for elections was urged according to the text of Organic Law No. 19-07 of 14 Muharram 1441 corresponding to September 14, 2019. The electoral process within the framework of a true embodiment of democracy and the authority of the people in Akhtia Representatives.